2020
DOI: 10.21873/invivo.11800
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Physical Training on the Levels of Sex Hormones and the Expression of Their Receptors in Rats With Induced Mammary Cancer in Secondary Prevention Model – Preliminary Study

Abstract: Background/Aim: Breast cancer is the most common malignant tumor among women worldwide. In previous work, we presented results of physical activity in primary prevention in a model of induced mammary gland cancer. In the present study, we assessed the influence of physical activity on sex hormone levels (estradiol and progesterone) and the expression of their receptors (ER, PR), as well as the level of apoptosis of tumor cells in secondary prevention. Materials and Methods: Fifty 1-month-old female Sprague-Daw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Among the included studies, 21 studies ( Steiner et al, 2013 ; Shalamzari et al, 2014 ; Alvarado et al, 2017 ; Alizadeh et al, 2018 ; Murphy et al, 2011 ; Aveseh et al, 2015 ; Leila et al, 2015 ; Malicka et al, 2015 ; Isanejad et al, 2016 ; Cui, 2017 ; Nasiri et al, 2017 ; Lyv Di et al, 2021 ; Qi et al, 2013 ; Siewierska et al, 2018 ; Siewierska et al, 2020 ; Wen et al, 2010 ; Gholamian et al, 2020 ; Vulczak et al, 2020 ; Wennerberg et al, 2020 ) reported that exercise could decrease the tumor volume, 1 ( Faustino-Rocha et al, 2016 ) reported negative effects of exercise, and 2 ( Smeda et al, 2017 ; Garritson et al, 2019 ) reported that exercise had no effect on the tumor volume.…”
Section: Resultsmentioning
confidence: 99%
“…Among the included studies, 21 studies ( Steiner et al, 2013 ; Shalamzari et al, 2014 ; Alvarado et al, 2017 ; Alizadeh et al, 2018 ; Murphy et al, 2011 ; Aveseh et al, 2015 ; Leila et al, 2015 ; Malicka et al, 2015 ; Isanejad et al, 2016 ; Cui, 2017 ; Nasiri et al, 2017 ; Lyv Di et al, 2021 ; Qi et al, 2013 ; Siewierska et al, 2018 ; Siewierska et al, 2020 ; Wen et al, 2010 ; Gholamian et al, 2020 ; Vulczak et al, 2020 ; Wennerberg et al, 2020 ) reported that exercise could decrease the tumor volume, 1 ( Faustino-Rocha et al, 2016 ) reported negative effects of exercise, and 2 ( Smeda et al, 2017 ; Garritson et al, 2019 ) reported that exercise had no effect on the tumor volume.…”
Section: Resultsmentioning
confidence: 99%
“…To date, it is still a challenge to estimate the magnitude of the clinical impact of PA on the observed levels of sex hormones, since there are no absolute cut-off values defined that correspond with a certain change in future BC risk and disease progression. However, besides an important effect on circulating sex hormone levels, it should also be considered that different studies on pre-clinical BC animal models demonstrate an important effect of PA to increase the ERβ/ERα ratio, as well as an increase in mammary gland cell apoptosis [ 41 , 176 , 177 ].…”
Section: Discussionmentioning
confidence: 99%
“…To date, few studies performed in rat models following physical training analyzed the expression of ER in BC cells. In these studies, authors demonstrated an effect of PA in increasing the ratio of ERβ/ERα, and a reduction in the sensitivity of BC cells to the pro-proliferative and antiapoptotic effects of estrogen, leading to apoptotic cell death [ 41 ].…”
Section: Estrogen Receptors In Breast Cancer and Their Clinical Implicationsmentioning
confidence: 99%